Answer:
The equation that would be used for the zero product property on will be (x-5)(x-10)=0
Option B is correct.
Explanation:
We need to solve the equation
![(1)/((x-4))+1=(14)/(x+2)](https://img.qammunity.org/2021/formulas/mathematics/college/39zk6wk2jjx98ketchweoqwkyr9hfi3ait.png)
Solving the equation:
![(1)/((x-4))+1=(14)/(x+2)\\(1+(x-4))/(x-4)= (14)/(x+2)\\(1+x-4)/(x-4)= (14)/(x+2)\\(x-3)/(x-4)= (14)/(x+2)\\Cross\: Multiply\\(x-3)(x+2)=14(x-4)\\x(x+2)-3(x+2)=14x-56\\x^2+2x-3x-6=14x-56\\x^2-x-6-14x+56=0\\x^2-x-14x-6+50=0\\x^2-15x+50=0](https://img.qammunity.org/2021/formulas/mathematics/college/lmp8pzi18e5ctapmsr3pp7gybwdhwn0gq0.png)
Now, we would factorise to find value of x
![x^2-15x+50=0\\x^2-5x-10x+50=0\\x(x-5)-10(x-5)=0\\(x-5)(x-10)=0](https://img.qammunity.org/2021/formulas/mathematics/college/cgwhn38qzbu4eeiioyre46wk1uswxi5p8g.png)
So, the equation that would be used for the zero product property on will be (x-5)(x-10)=0
Option B is correct.